Empirical essays on fiscal federalism and political economy in Germany - Manuela Krause (ifo Institut – Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2019)
The dissertation consists of six self-contained chapters that are related to selected incentives in fiscal federalism by using the example of the federal system in Germany. The dissertation elaborates on political as well as fiscal incentives. Chapters 2 and 3 examine election cycles, based on the political business cycle theories. Chapter 2 examines whether election cycles occur in fees of German municipalities. The results show that municipalities have a leeway to decide on fees and use this leeway to improve election prospects. Chapter 3 investigates election cycles in salary increases of German state MPs, for which the states have the decision-making authority. The results do not show that electoral motives influence increases in MP salaries. Chapters 4 and 5 investigate how government ideology influences economic policy-making. Chapter 4 analyzes whether government ideology influences income inequality in the public sector of the German states by using data on salaries of civil servants. The results do not show that left-wing governments were more active in decreasing income inequality in the public sector than center or right-wing governments. Chapter 5 analyzes whether government ideology predicts tax policies of the German states. A reform of the fiscal constitution in 2006 allowed the states to set the tax rates of the real-estate transfer tax. By investigating the tax rate increases of the German states, the results show that left-wing governments were more active in increasing the tax rates than right-wing governments. Chapters 6 and 7 investigate fiscal incentives within the federal system in Germany by analyzing whether the institutional setting also provides incentives for states' tax policies. The German fiscal equalization scheme redistributes revenues among the federal and state level and between states equalizing funds for the states. The devolution of tax setting powers to the states in 2006 provides an interesting set-up to investigate the combination of tax autonomy and fiscal equalization. The descriptive results in Chapter 6 and the empirical analysis in Chapter 7 show that equalization substantially influences tax policies of the states. The redistribution of revenues within the equalization scheme provides incentives for the states to raise rather than to lower their tax rates. – – Die Dissertation behandelt in sechs eigenständigen Kapiteln ausgewählte Anreize im Fiskalföderalismus am Beispiel des föderalen Systems in Deutschland. Dabei werden sowohl politische als auch fiskalische Anreize in den Blick genommen. In Kapitel 2 und 3 wird basierend auf den Theorien zu politischen Konjunkturzyklen das Vorliegen von Wahlzyklen analysiert. In Kapitel 2 wird untersucht, ob sich Wahlzyklen in Benutzungsgebühren von deutschen Gemeinden identifizieren lassen. Die Ergebnisse zeigen, dass Gemeinden einen politischen Entscheidungsspielraum hinsichtlich ihrer Gebühren haben und diesen auch nutzen, um ihre Wahlchancen zu verbessern. In Kapitel 3 werden Diätenerhöhungen von Landtagsabgeordneten analysiert, für welche die deutschen Bundesländer ebenfalls einen Entscheidungsspielraum haben. Die Ergebnisse deuten hier allerdings nicht auf einen Wahlzyklus hin. Kapitel 4 und 5 untersuchen, ob die Regierungsideologie die Handlungsmotive von Politikern beeinflusst. In Kapitel 4 wird analysiert, ob die Regierungsideologie einen Einfluss auf die Einkommensungleichheit im öffentlichen Sektor der Länder hat. Dabei werden Daten zu Gehältern von Landesbeamten genutzt. Die Ergebnisse zeigen nicht, dass linke Regierungen aktiver in einer Reduzierung der Einkommensungleichheit sind als konservative Regierungen. In Kapitel 5 wird untersucht, ob die Regierungsideologie die Steuerpolitik der deutschen Bundesländer beeinflusst. Im Zuge der Föderalismusreform im Jahr 2006 erhielten die Länder die Möglichkeit, den Steuersatz der Grunderwerbsteuer selber zu bestimmen. Eine Analyse der Steuersatzerhöhungen seit dieser Reform zeigt, dass linke Regierungen die Steuersätze der Grunderwerbsteuer aktiver erhöht haben als rechte Regierungen. Kapitel 6 und 7 untersuchen fiskalische Anreize im föderalen System in Deutschland. Im Fokus steht dabei eine Analyse der Anreize von institutionellen Rahmenbedingungen auf die Steuerpolitik der Länder. Das System des Finanzausgleichs verteilt finanzielle Mittel zwischen Bund und Ländern sowie zwischen den Ländern um mit dem Ziel, die Finanzkraftunterschiede unter den Ländern auszugleichen. Die im Zuge der Föderalismusreform auf die Länder übertragene Möglichkeit, den Steuersatz der Grunderwerbsteuer zu bestimmen, bietet eine vielversprechende Grundlage, um die Kombination von Steuerautonomie und Finanzausgleich zu analysieren. Die deskriptiven Ergebnisse in Kapitel 6 und die empirische Analyse in Kapitel 7 zeigen, dass der Finanzausgleich substantielle Effekte auf die Steuerpolitik der Länder hat. Die Umverteilung von Einkommen im Finanzausgleich erzeugt Anreize für die Länder, ihre Steuersätze immer weiter zu erhöhen.
Keywords: 330